Training through Tasks: Voices of Medical Professionals on English Learning at RS Haji Medan - Ariatna; Anggraini Thesisia Saragih; Rika; Yuni Khairina; Fitri Ayu (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This study explores the implementation of a Task-Based Language Teaching (TBLT) English training program for medical staff at RS Haji Medan, a government-owned hospital in North Sumatra, Indonesia, aiming for Joint Commission International (JCI) accreditation. Despite having strong infrastructure, the hospital faces challenges in English communication among staff, which is critical for serving international patients. The training program involved 15 doctors, nurses, and administrative staff, focusing on practical communication in clinical settings through simulations, problem-solving, and medical dialogues. At the end of the program, a 5-point Likert scale questionnaire was administered to obtain students’ views on the task-based instruction. The survey data revealed positive responses regarding material relevance, teaching methods, instructor performance, and the usefulness of learning resources. Most participants reported improved English skills and greater confidence in medical communication. The findings highlight TBLT's effectiveness in meeting specific workplace needs and support its broader use in healthcare language training. This study contributes to the growing English for Specific Purposes (ESP) field in Indonesian medical contexts.